STUDI KOMPARASI PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL MELALUI MEDIASI DAN KONSILIASI - Sastiono Kesek (Prodi Ilmu Administrasi Negara, 2015)
Since the birth of Law No. 2 of 2004 concerning about industrial disputes settlement, the parties to the dispute becomes easier and aided in order to settle a dispute between them. Instrument provided also become more diverse compared to the old rules. Like instrument of mediation, conciliation and arbitration. However, in the application stage, not many people understand the difference between the disputing mediation and conciliation which in terms of the origin and function of mediation from conciliation has a characteristic that varies as a mediator in the nature of a passive mediation while in conciliation konsiliatornya more active in resolving disputes. In the settlement of industrial disputes mediation is used as the main instrument for solving broader scope than conciliation. Mediation can handle disputes over rights, interests, employment termination (PHK) and disputes between unions in one company. Conciliation made limited progress on conflict of interest, termination of employment disputes and disputes between unions in one company. Although in reality most of the industrial dispute that involves a dispute over rights. The writing instrument of mediation and conciliation mengkomparasi comprehensively describe the advantages and disadvantages of each such instrument.